Cara Mudah Membangun Website Menggunakan Wordpress - Rahayu Sri Sulistyawati (IKIP PGRI Pontianak, 2012)
Wordpress is an open source application (open source) are very popular used as a blog engine (blog engine). Wordpress is built with PHP programming language and database (the database) My SQL. PHP and MySQL, both of which are open source software (open source software). In addition to the blog, is also starting to use Wordpress as a CMS (Content Management System) for its ability to be modified and adapted to the needs of users. Wordpress is the official successor of b2/cafelog developed by Michel Valdrighi. The name Wordpress was proposed by Christine Selleck, a friend of chairman of the developer (developer), Matt Mullenweg. The latest release of Wordpress is version 3.4.2 (9 September 2012). Wordpress is distributed with teh GNU General Public License. Keywords: Website, Wordpress